Character Education and Student Morality : An Analysis of Personal Commitment, Goal Orientation, and Self-Efficacy - Mursidin Mursidin (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This research aims to analyze the impact of personal commitment and goal orientation with self-efficacy as a mediating factor on student moral behavior in character education at the Sunan Gunung Djati State Islamic University, Bandung. Self-efficacy serves as a mediating factor in this examination. The study used a quantitative approach with a survey method, and data analysis was executed through path analysis using the SPSS software. The data was collected using a questionnaire distributed to 100 students. Findings from this research indicated that moral conduct was a multifaceted variable influenced by various factors, whether directly or indirectly, internally, or externally. This study discerned that personal commitment, Goal Orientation, and Self-efficacy wield both direct and indirect influenced over students' moral behavior. Furthermore, Self-efficacy assumed a pivotal mediating role in delineating the connection between personal commitment, Goal Orientation, and students' moral conduct.